Pengaruh Independensi, Komitmen Organisasi dan Gaya Kepemimpinan Transformasional pada Kinerja Auditor di Kantor Akuntan Publik Se-Provinsi Bali - Kusuma, Ida Bagus Kade Diva Jati Darma; Widhiyani, Ni Luh Sari (BUDGETING : Journal of Business, Management and Accounting, 2023)
Many cases are caused by the auditor's lack of ability to detect fraud in financial reports, resulting in losses that have a negative impact on various parties involved in the company. With this case, it is feared that users of financial information will doubt the information presented in audited reports and this could lead to a crisis of confidence and loss of credibility for the public accounting profession in processing and presenting financial information. This research was conducted to determine the influence of independence, organizational commitment and transformational leadership style on the performance of auditors in Public Accounting Firms throughout Bali Province. The theoretical basis in this research is the theory of attitudes and behavior. The sample in this study was 62 auditors at 10 public accounting firms in Bali Province. In this research, data collection was carried out by distributing questionnaires to 10 Public Accounting Firms in Bali Province and given to 64 Auditors. The sample used in this research was the purposive sampling method. The data analysis method used is multiple linear regression analysis. This research supports the theory of attitudes and behavior. This research is closely related to attitude and behavior theory which can explain how independence, organizational commitment and transformational leadership style influence auditor performance. Research shows that independence, organizational commitment and transformational leadership style have a positive effect on auditor performance. If the auditor's independence, organizational commitment and transformational leadership style are higher, the auditor's performance will be better. Keywords: Auditor Performanc, Independence, Organizational Commitment, Transformational Leadership Style, Public Accountant